Natural Dyeing of Silk Fabric Using Eco-Friendly Mordants - Sundrarajan, M.; Rajiv gandhi, R.; Suresh, J.; Gowri, S.; Selvam, S. (Asian Journal of Chemistry, 2012)
Parijataka dye (Nyctanthes arbor-tristis), which is a natural colourant extracted from orange corolla tube of parijataka flowers were studied for their dyeing potential on silk with a variety of mordants. Colour of the pigment was fixed by the utilization of eco-friendly mordants like SnCl2, CuSO4, FeSO4, K2Cr2O7, pomegranate, tannin, alum and lime juice. Some of the mordants used are new for parijataka dyeing. Among the various mordanting method simultaneous mordanting method was the most suitable one for dyeing of parijataka on silk. The range of colour developed on dyed materials are evaluated (in terms L*, a*, b*) and the improvement of colour strength on fabric by mordants were also examined. Dye ability was more in unmordant and lime juice mordanted silk fabric. The colour strength (K/S) and wash fastness values has been found to be good in all dyed samples especially SnCl2, alum and lime juice mordanted fabrics.